Non-Invasive Ventilation in COVID-19 Related Respiratory Failure - Irmi Syafa'ah; Young-Jae Cho (Faculty of Medicine Universitas Airlangga, 2021)
Non-invasive ventilation (NIV) provides mechanical ventilation that does not require definitive airway clearance using an endotracheal tube or tracheostomy. Since its early development in the 1980s, the use of NIV has become increasingly popular in the last three decades. However, its usage on COVID-19-related respiratory failure still lacks guidelines, although several recent studies have shown its benefits. Many aspects, ranging from indications or patient selection, timing to start, understanding the predictor factors of failure, and choosing suitable interfaces, are keys of success for NIV. In principle, each patient has a different condition and should be treated case by case. NIV is not an absolute solution, and intubation can still be the first choice if NIV is deemed less beneficial for the patient.